Avian bornavirus in the urine of infected birds - Villalobos AR (Dove Medical Press, 2012)
J Jill Heatley,1 Alice R Villalobos21Zoological Medicine, 2Department of Nutrition & Food Science, Texas A&M University, College of Veterinary Medicine and Biomedical Sciences, College Station, TX, USAAbstract: Avian bornavirus (ABV) causes proventricular dilatation disease in multiple avian species. In severe clinical disease, the virus, while primarily neurotropic, can be detected in many organs, including the kidneys. We postulated that ABV could be shed by the kidneys and found in the urine of infected birds. Immunohistochemical staining demonstrated viral N and P proteins of ABV within the renal tubules. We adapted a nonsurgical method of urine collection for use in parrots known to be shedding ABV in their droppings. We obtained urine without feces, and results were compared with swabs of fresh voided feces. Reverse transcription–polymerase chain reaction assay performed on these paired samples from five birds indicated that ABV was shed in quantity in the urine of infected birds, and a single sample was urine-positive and fecal-negative. We suggest that urine sampling may be a superior sample for detection of birds shedding ABV, and advocate that additional birds, known to be shedding or infected with ABV, should be investigated via this method.Keywords: avian bornavirus, Psittaciformes, parrot, urine, proventricular dilatation disease